Application of the single-minute exchange of die system to the CNC sector of a shoe mold company. Issue 1 (1st January 2019) - Ribeiro, Rodrigo Borges; Souza, José De; Beluco, Alexandre; Biehl, Luciano Volcanoglo; Braz Medeiros, Jorge Luiz; Sporket, Frederico; Rossini, Elton Gimenez; Amaral, Fábio Augusto Dornelles Do
Abstract: The aim of this work is to present a quantitative evaluation of the benefits of applying the Single-Minute Exchange of Die (SMED) implemented in a shoe mold company. Based on the application of this methodology, we noticed that real gains were obtained with very little financial investment. The improvements observed in the sector were the reduction of set-up time by 60%, with an average set-up time of approximately 7 min, and an increase in the productive capacity of the sector by around 3%. There was a reduction in the incidence of errors in the machined parts due to the standardization of the processes performed by the operators. Among the advantages presented with the new system are reduced material exchange time, reduced time spent fine-tuning, less chance of errors during exchanges, improved product quality, greater reliability with respect to reduction of dissociation stocks and the flexibilization of the production system.